Undergraduate public health degree courses in India: selected overview - Joshi, Vibha; Joshi, Nitin Kumar; Bajaj, Komal; Suthar, Praveen; Fant, Gregory; Purohit, Anil (International Journal Of Community Medicine And Public Health, 2019)
Background: Building the public health workforce in India along with strengthening the public health systems across the Nation are essential components necessary to achieve the sustainable development goals for India. In the Indian context, there is limited information available for undergraduate public health education. The central aim of this brief study is to elucidate the undergraduate public health education landscape at selected institutions in India. Methods: A mixed methods approach was used in this brief study. First, cross-sectional, scoping review was used. Then, to describe student perceptions and attitude towards undergraduate public health curriculum, primary data were collected by using a questionnaire. A self-administered questionnaire was developed after extensive literature search. Descriptive statistics were used to summarize questionnaire results. Chi-square tests were used to help identify factors that may influence student perceptions and attitudes. Results: Through scoping rapid review and internet search, eight institutions were identified that are offering undergraduate public health courses in India. Most institutes in India have 3 years duration for the undergraduate public health degree courses. Most of students (89%) believed that the undergraduate public health course increased their knowledge in the field of public health. We found an association between student perceptions about community benefits from trained undergraduate public health workforce. Conclusions: The undergraduate public health education initiatives should be promoted and envisioned as a new strategy for public health capacity-building in public health in India.